Independent and sensory human mitochondrial functions reflecting symbiotic evolution - Stefano, George B.; Büttiker, Pascal; Weissenberger, Simon; Esch, Tobias; Anders, Martin; Raboch, Jiri; Kream, Richard M.; Ptacek, Radek (Frontiers in Cellular and Infection Microbiology, 2023)
The bacterial origin of mitochondria has been a widely accepted as an event that occurred about 1.45 billion years ago and endowed cells with internal energy producing organelle. Thus, mitochondria have traditionally been viewed as subcellular organelle as any other – fully functionally dependent on the cell it is a part of. However, recent studies have given us evidence that mitochondria are more functionally independent than other organelles, as they can function outside the cells, engage in complex “social” interactions, and communicate with each other as well as other cellular components, bacteria and viruses. Furthermore, mitochondria move, assemble and organize upon sensing different environmental cues, using a process akin to bacterial quorum sensing. Therefore, taking all these lines of evidence into account we hypothesize that mitochondria need to be viewed and studied from a perspective of a more functionally independent entity. This view of mitochondria may lead to new insights into their biological function, and inform new strategies for treatment of disease associated with mitochondrial dysfunction.